Merancang Pembelajaran Sejarah yang Inovatif Melalui Pendekatan Proyek (Project-Based Learning): Designing Innovative History Learning Through a Project-Based Learning Approach - Febriyanti, Intan; M. Al Aziz Akbar; Anggita Novi Arianti; Sani Safitri; Rani Oktapiani (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study discusses the implementation of Project-Based Learning (PjBL) in history education as an effort to improve motivation, learning outcomes, and strengthen the character traits of the Pancasila Student Profile, which include collaboration, mutual cooperation, and critical thinking. In response to the challenges of 21st-century education and the development of digital technology, teachers are required to create innovative, interactive, and relevant history learning experiences that are enjoyable and connected to students’ real-life contexts. The theoretical foundations of constructivism, experiential learning, and social-collaborative theory indicate that PjBL is effective in encouraging students to build knowledge through research, discussion, and independent exploration of historical sources. Findings from various empirical studies show that PjBL increases students’ motivation, participation, and conceptual understanding, while also strengthening historical literacy skills through source analysis, field observation, and the creation of historical products. PjBL has also been proven to develop 21st-century skills such as creativity, communication, critical thinking, and group collaboration that reflect the value of mutual cooperation. On the other hand, this study identifies several implementation challenges, including limited time, insufficient technological facilities, low initial student motivation, and minimal parental support. Nevertheless, integrating PjBL with the values of the Pancasila Student Profile within local history projects has been shown to shape students’ social-intellectual character while improving the quality of history learning. Therefore, PjBL is deemed appropriate as a primary approach for developing history education in the Merdeka Curriculum.